Answer:
3, 3 and 1
Step-by-step explanation:
Using the rule of exponents
[tex]a^{m}[/tex] × [tex]a^{n}[/tex] = [tex]a^{(m+n)}[/tex]
Given
([tex]x^{-3}[/tex] [tex]y^{5}[/tex] [tex]z^{-4}[/tex] × [tex]x^{6}[/tex] [tex]y^{-7}[/tex] [tex]z^{-2}[/tex]
A
[tex]x^{-3}[/tex] × [tex]x^{6}[/tex] = [tex]x^{(-3+6)}[/tex] = x³ → with exponent 3
B
[tex]y^{5}[/tex] × [tex]y^{-7}[/tex] = [tex]y^{(5-7)}[/tex] = [tex]y^{-2}[/tex] → with exponent - 2
C
[tex]z^{-4}[/tex] × [tex]z^{-2}[/tex] = [tex]z^{(-4-2)}[/tex] = [tex]z^{-6}[/tex] → with exponent - 6